ОЦІНКА ТОЧНОСТІ РЕГУЛЮВАННЯ СТРУМУ БАГАТОКОМІРКОВОГО ТРАНЗИСТОРНОГО ПЕРЕТВОРЮВАЧА З КОМБІНОВАНИМ КЕРУВАННЯМ - Бондаренко, Ю.В.; Сидорець, В.М.; Сафронов, П.С.; Бондаренко, О.Ф. (Інститут електродинаміки НАН України, Київ, 2012)
The simulation of multicell-type transistor converter with common use of continuous and pulse control for current regulation in micro resistance welding machines is carried out. The accuracy of reference signal tracking by converter is evaluated with simulation. References 2, figures 2.